Quotation and cultural meaning in twentieth-century music - Metzer, David (Cambridge Cambridge University Press, 2003)
Throughout the twentieth century, musicians frequently incorporated bits of works by other musicians into their own compositions and performances. When a musician borrows from a piece, he or she draws upon not only a melody but also the cultural associations of the original piece. By working with and altering a melody, a musician also transforms those associations. This book explores that vibrant practice, examining how musicians used quotation to participate in the cultural dialogues sustained around such areas as race, childhood, madness and the mass media. The focus of this study is broad, discussing pieces in a spectrum of musical styles (classical, experimental, jazz, and popular) as well as works in the other arts. Part of the young and quickly growing field of musical borrowing, this book takes an important step in discussing the wider cultural ramifications of quotation.